2001
DOI: 10.1159/000053932
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency Retroviral Transduction of Fetal Liver CD38–CD34++ Cells: Implications for in utero and ex utero Gene Therapy

Abstract: Objectives: Defining methods for the efficient transduction of fetal stem cells could lead to novel fetal therapies for blood cell disorders and other birth defects. In this study, we analyzed the effects of various parameters on the retroviral transduction of primitive hematopoietic progenitors/stem cells isolated from fetal liver. Methods: Candidate stem cells were isolated by fluorescence-activated cell sorting from midtrimester human livers based on the phenotype CD38–CD34++lineage– (lineage = glycophorin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…It is known that fetal development results in rapid liver growth [42] , and therefore its size, accessibility, and straightforward localization in the fetal rabbits makes this organ a good target for gene transfer. Moreover, it has been recently shown that fetal liver stem cells can undergo effi cient retroviral vector-mediated gene transfer ex vivo [43] . Likewise, a recent report has also demonstrated that lentiviral vector transduction effi ciency and transgene expression into hepatocytes in vivo is signifi cantly enhanced at early developmental stages [44] .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that fetal development results in rapid liver growth [42] , and therefore its size, accessibility, and straightforward localization in the fetal rabbits makes this organ a good target for gene transfer. Moreover, it has been recently shown that fetal liver stem cells can undergo effi cient retroviral vector-mediated gene transfer ex vivo [43] . Likewise, a recent report has also demonstrated that lentiviral vector transduction effi ciency and transgene expression into hepatocytes in vivo is signifi cantly enhanced at early developmental stages [44] .…”
Section: Discussionmentioning
confidence: 99%
“…29,30 In addition, experimental studies with the ovine model showed the possibility of collecting fetal liver cells in sufficient numbers for the autologous transplantation of the animals. 31 The combined use of ex vivo HSC gene therapy and IUT may improve the therapeutic potential of both strategies used as individual therapies, thus facilitating the treatment of diseases diagnosed during fetal development.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of MGDF has also been shown to increase the mobilization of progenitors and stem cells (40 -42). Gene therapy performed on hematopoietic stem cells isolated from fetal and/or neonatal blood is being studied as a means to treat a number of inherited disorders of the hematopoi-1055 GROWTH OF FETAL PROGENITORS WITH MGDF etic system (43)(44)(45)(46)(47). Mobilization of stem cells by MGDF administration may increase the yield of stem cells that can be harvested for therapy and returned to the fetal or neonatal circulation.…”
Section: Linmentioning
confidence: 99%